Click to Chat

1800-1023-196

+91-120-4616500

CART 0

• 0

MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping
`        Give Brief solution of the question in the attachment. `
9 months ago

```							from binomial theorem,(1+x)^100= 100C0 + 100C1*x + 100C2x^2 + 100C3*x^3 + …........in the above identity, put x= 1, w, w^2 successively (where w and w^2 are the complex cube roots of unity, as we know that roots of z^3= 1 are 1, w, w^2)so, 2^100= 100C0 + 100C1 + 100C2 + 100C3 + …........and (1+w)^100= 100C0 + 100C1*w + 100C2w^2 + 100C3*w^3 + …........and (1+w^2)^100= 100C0 + 100C1*w^2 + 100C2w^4 + 100C3*w^6 + …........adding these 3 eqns,2^100 + (1+w)^100 + (1+w^2)^100= 3*100C0 + 100C1*(1+w+w^2) + 100C2*(1+w^2+w^4) + 100C3*(1+1+1) + ….....or 2^100 + (1+w)^100 + (1+w^2)^100= 3*100C0 + 0 + 0 + 3*100C3 + 0 + …..............(because w^3= 1 and 1+w+w^2= 0)or  2^100 + (1+w)^100 + (1+w^2)^100= 3(100C0 + 100C3 + …......)so, 100C0 + 100C3 + ….....= (2^100 + (1+w)^100 + (1+w^2)^100)/3so, we just need to find value of (1+w)^100 + (1+w^2)^100= ( – w^2)^100 + ( – w)^100 [using 1+w+w^2= 0]= w^200 + w^100= w^100(1+w^100)= w^100(1+(w^3)^33*w)= w^100(1+w)= w^100( – w^2)= – w^102= – (w^3)^34= – 1so, final ans is (2^100 – 1)/3kindly approve :=)
```
9 months ago
Think You Can Provide A Better Answer ?

## Other Related Questions on Algebra

View all Questions »  ### Course Features

• 731 Video Lectures
• Revision Notes
• Previous Year Papers
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Test paper with Video Solution  ### Course Features

• 101 Video Lectures
• Revision Notes
• Test paper with Video Solution
• Mind Map
• Study Planner
• NCERT Solutions
• Discussion Forum
• Previous Year Exam Questions